STUDI ANALISIS PEMIKIRAN SITI WALIDAH (NYAI AHMAD DAHLAN) DALAM PENDIDIKAN PEREMPUAN - Halimatussa’diyah Nasution; Syamsu Nahar; Ali Imran Sinaga (UIN Sumatera Utara Medan, 2019)
This thesis aims to describe and analyze: (1) social conditions which aspects influenced the thinking of Siti Walidah (Nyai Ahmad Dahlan) against the education of women. (2) the contribution of the female education thinking according to Siti Walidah (Nyai Ahmad Dahlan), (3) relevance to education of women at this time. This type of research is qualitative research in the design of the library (library research), using the approach of the study of character, and technical analysis of the data used is the technique of triangulation.The research results showed that: 1. The background to the life of Siti Walidah (Nyai Ahmad Dahlan), next as a housewife, she also encouraged women to follow education equivalent to men so that the necessary container for develop writing, 2. The contribution of Siti Walidah (Nyai Ahmad Dahlan) in setting up the Organization for women aims to provide education to the children of women particularly in Kauman of Yogyakarta, the influence of organizations capable of providing inspiration Aisyiyah for the females to education, particularly for the development of model education of women at this time